Människan som individ i sociala systems omvärld. Om individ och person i Niklas Luhmanns systemteori (Sociologisk Forskning, 1995)
Man as individual in the environment of social systems. On individual and person in Niklas Luhmann's systems theoryThe relation between man and society is an old and central problem in the modem social sciences. Traditionally, man has been seen as a part of society. Luhmann’s main thesis, contrary to the sociological tradition, is that man as individual always belongs to an environment of social systems. The intention of this article is to present Luhmann’s analysis, and at the same time to discuss it in relation to the sociological theoretical tradition and to show its actuality. Luhmann’s analysis follows four main lines: First, the difference between social and psychic systems is clarified as distinctions; secondly, the obvious connections between these systems has to be defined. This is done through the concept of structural coupling and specified in terms of interpenetration, socialization, inclusion and exclusion, a third way of analysis focuses on the concept of person. Only as person is man part of a social system, and as such takes on and breaks roles and other social relations. Finally, the modem individuality is focused upon. Humanistic philosophy, which has strongly influenced the social sciences, signifies the modem individual as a subject. This subject, on the one hand, complains of alienation, on the other hand, demands emancipation. Consequently, the subject is confrontedwith the paradox of too much and, at the same time, too little solidarity. From the point of view of social systems problems of individualization are problems of the environment of society and therefore not questions of solidarity. As employee, man is included in the economy as a functional system; as citizen in a democracy, he or she is included in a political system, etc. Without a job citizenship, etc, the individual is excluded from functional systems. The current growing global problems of the individual, in terms of unemployment, of homelessness, deplacement, etc, must be understood as beeing closely connected with the functional differentiation of society. By placing the individual in the environment of social systems, these societal and social problems can be analysed in a new way, and it implies, paradoxically, a concept of society more adapted to man than the one proclaimed by humanistic philosophy.